A Dynamic Model of Inflation for Kenya, 1974-1996 - Ndung'u, Njuguna; Durevall, Dick. (Washington, D.C. : International Monetary Fund, 1999)
This paper analyses the dynamics of inflation in Kenya during 1974-96, a period characterized by external shocks and internal disequilibria. By developing a parsimonious and empirically constant error correction model the paper finds that the exchange rate, foreign prices, and terms of trade have long-run effects on inflation, while the money supply and interest rate only have short-run effects. The dynamics of inflation are also found to be influenced by food supply constraints. Moreover, inertia is important for the period up to 1993, when about 40 percent of current inflation was transmitted to the next quarter. After 1993 inertia drops to about 10 percent.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet